Comparison of the Changes in Quality-of-Life of Cats with Hyperthyroidism Treated with Radioiodine or Antithyroid Drugs—A Preliminary Study - Fabienne Blunschi; Sofie Muthmann; Natali Bauer; Katarina Hazuchova (Veterinary Sciences)
A previous cross-sectional study found impaired health-related quality of life (HRQoL) in hyperthyroid cats, but the longitudinal impact of treatment—especially differences between radioiodine (RAIT) and antithyroid drug (ATD) approaches—remains unclear. This study aimed to evaluate changes in HRQoL in recently diagnosed (<6 months) hyperthyroid cats that underwent RAIT or received ATD. HRQoL was assessed using the validated HyperthyroidismQoL-cat questionnaire at baseline and after 1, 3, and 6 months, alongside thyroid status (eu-/hypo-/hyperthyroid) evaluation. Mixed-effects model analysed the influence of treatment type, timepoint, and thyroid status on log(HRQoL). HRQoL differences between groups at baseline and comparison to a non-hyperthyroid control group (n = 322) from a previous study at month 6 were examined using Mann–Whitney U tests. Data are presented as median (range), with significance set at p < 0.05. Thirty-eight client-owned hyperthyroid cats (15 ATD, 23 RAIT) were included. HRQoL scores at baseline did not differ between groups (RAIT: 103.5 [27–211], ATD: 73 [22–260], p = 0.22). HRQoL significantly improved over time (p < 0.001) but was not affected by treatment type (p = 0.20) or thyroid status (p = 0.40). Despite improvement, HRQoL remained lower than in non-hyperthyroid controls (hyperthyroid: 42.5 [3–161.5], non-hyperthyroid: 27 [0–249], p = 0.007). This study highlights the overall positive impact of treatment on HRQoL, but due to the lack of randomisation and heterogeneity of subjects and treatment, conclusion have to be considered preliminary.